TASK-BASED LANGUAGE LEARNING AND TEACHING IN EFL CLASSROOMS - Shermatova Sevara Azamjon qizi; Nabijonova Ruxshona Akmal qizi; Ibrohimova Mohinur O’tkir qizi; Sayfiyeva Gulsanam Sohibjon qizi (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This paper examines Task-Based Language Teaching (TBLT) as an effective approach in modern language education. It focuses on its key principles, benefits, and challenges, highlighting how meaningful tasks enhance communicative competence, learner engagement, and practical language use.